1989
DOI: 10.1101/gad.3.12b.2113
|View full text |Cite
|
Sign up to set email alerts
|

The organization of 3' splice-site sequences in mammalian introns.

Abstract: A model pre-mRNA substrate was used to carry out a detailed investigation of the functional organization of sequences at the 3' end of mammalian introns. This analysis revealed a difference in the sequence requirements for the first and second steps of the splicing reaction (lariat formation and exon ligation, respectively). Maximal efficiencies of lariat formation require a pyrimidine stretch directly adjacent to the branch site. In addition, efficient lariat formation can be specified in at least two distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
261
0
3

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(282 citation statements)
references
References 50 publications
(79 reference statements)
18
261
0
3
Order By: Relevance
“…This is consistent with the observation that two different S. pombe introns could not be converted to AG-independence by expansion of the polypyrimidine tract (Romfo and Wise, 1997), in contrast to AG-dependent mammalian substrates (Reed, 1989). Thus, the information content of the polypyrimidine tract alone is not sufficient for 3Ј splice site recruitment in S. pombe.…”
Section: U2af-dependence Does Not Correlate With Other Obvious Featursupporting
confidence: 79%
See 2 more Smart Citations
“…This is consistent with the observation that two different S. pombe introns could not be converted to AG-independence by expansion of the polypyrimidine tract (Romfo and Wise, 1997), in contrast to AG-dependent mammalian substrates (Reed, 1989). Thus, the information content of the polypyrimidine tract alone is not sufficient for 3Ј splice site recruitment in S. pombe.…”
Section: U2af-dependence Does Not Correlate With Other Obvious Featursupporting
confidence: 79%
“…The bipartite nature of the RNA target sequences for the two subunits, in combination with biochemical complementation data demonstrating that addition of the human large subunit (hsU2AF LG ) alone to U2AF-depleted HeLa nuclear extracts can rescue splicing of substrates that contain long polypyrimidine tracts (Wu et al, 1999;Guth et al, 2001), led to a widely accepted model for 3Ј splice site recognition by U2AF. The central tenet of this model is that the binding energy contributed by the small subunit/AG interaction is essential only for introns with less extensive polypyrimidine tracts (reviewed in Moore, 2000), consistent with earlier splicing assays of mutant human pre-mRNAs in vitro, which indicated that the requirement for a 3Ј AG to proceed through the first step of splicing (AG-dependence) could be eliminated by expanding the polypyrimidine tract (Reed, 1989). In S. pombe, mutating the terminal AG dinucleotide prevented the first transesterification reaction for all three introns examined (Romfo and Wise, 1997), as for a subset of mammalian pre-mRNAs (Reed, 1989;Wu et al, 1999).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The requirement for U2AF 35 in pre-mRNA splicing has been unclear for many years+ As mentioned above, dU2AF 38 is required for viability (Rudner et al+, 1996), as is its interaction with dU2AF 50 (Rudner et al+, 1998c)+ It is clear from in vitro assays that it can be dispensable for constitutive splicing under certain conditions (Zamore & Green, 1991;Zhu & Krainer, 2000), although it has also been shown to be required (Zuo & Maniatis, 1996;Zhu & Krainer, 2000)+ The recent discovery that U2AF 35 interacts with the 39 splice site AG (Merendino et al+, 1999;Wu et al+, 1999;Zorio & Blumenthal, 1999) may resolve some of these issues+ U2AF 35 does not appear to be essential for the splicing of AG-independent introns (Wu et al+, 1999)-introns containing a strong pyrimidine tract (Reed, 1989)+ However, U2AF 35 is required for the splicing of AG-dependent introns (Wu et al+, 1999)-introns that contain short or weak pyrimidine tracts (Reed, 1989)+ With regards to enhancer-dependent splicing, U2AF 35 has been reported to be both dispensable (Kan & Green, 1999) and essential (Zuo & Maniatis, 1996;Guth et al+, 1999)+ In addition, U2AF 35 has been shown to be both required for (Zuo & Maniatis, 1996) and dispensable for (Guth et al+, 1999;Kan & Green, 1999) enhancerdependent U2AF 65 crosslinking+ Here we have shown that although U2AF 35 is not absolutely required for enhancer-dependent splicing, it does enhance the activity of U2AF for both the dsx and IgM pre-mRNAs+ We also have shown that the splicing activators stimulate the binding of U2AF 35 to the pre-mRNA, presumably to the AG at the 39 splice site (Merendino et al+, 1999;Wu et al+, 1999;Zorio & Blumenthal, 1999)+ We believe that U2AF 35 has two important functions that can increase the activity of U2AF in certain circumstances+ First, because U2AF 35 can bind the 39 splice site (Merendino et al+, 1999;Wu et al+, 1999;Zorio & Blumenthal, 1999), its association with U2AF 65 provides at least one additional protein-RNA contact when compared to U2AF 65 alone+ In fact, the binding affinity of the U2AF 65/35 heterodimer for RNA is greater than that of U2AF 65 alone (Rudner et...…”
Section: The Role Of U2af 35 In Enhancer-dependent Splicingmentioning
confidence: 99%
“…The role of the 39 splice site AG in early steps of splicing is less clear+ Single base mutations or deletion of the 39 splice site AG dinucleotide of the first intron of the human b-globin gene allow lariat intermediate formation to proceed but inhibit the second step of splicing (Reed & Maniatis, 1985;Ruskin & Green, 1985)+ Recently, a bimolecular exon ligation assay has been established in which a substrate containing the 59 splice site and BP sequence is joined to a substrate containing a 39 exon preceded by an AG dinucleotide (Anderson & Moore, 1997)+ In this system the 59 exon-intron substrate can undergo 59 splice site cleavage and lariat formation in the absence of the 39 substrate containing the 39 splice site AG+ However, in other systems, mutations or chemical modifications of the AG dinucleotide greatly impair spliceosome assembly and lariat intermediate formation, implying a role for the 39 splice site AG before the first step of splicing (Aebi et al+, 1986;Lamond et al+, 1987;Lang & Keller, 1990)+ It has been suggested that the importance of the AG sequence is more pronounced if the length of the polypyrimidine tract is relatively short (Reed, 1989)+ We find a high conservation of AG dinucleotides in the selected pool indicating that the presence of a 39 splice site-like element greatly improves the chances of proceeding through the first step of splicing, even in the presence of an optimal polypyrimidine tract+ Analysis of an RNA clone containing a point mutation of the guanosine nucleotide in the 39 end of the intron confirmed that this nucleotide is already important at or before the level of complex A formation+ Clearly, the definition of the BP in our construct is a combined action of multiple interactions involving the BP region itself, the polypyrimidine tract, and the AG dinucleotide at the 39 splice site+…”
Section: Selection Of Polypyrimidine Tracts and 39 Splice Sitesmentioning
confidence: 99%